How Much Better Are the Most-Prestigious Journals? The Statistics of Academic Publication - Starbuck, William H. (Organization Science, 2005)
Articles in high-prestige journals receive more citations and more applause than articles in less-prestigious journals, but how much more do these articles contribute to knowledge? This article uses a statistical theory of review processes to draw inferences about differences value between articles in more-prestigious versus less-prestigious journals. This analysis indicates that there is much overlap in articles in different prestige strata. Indeed, theory implies that about half of the articles published are not among the best ones submitted to those journals, and some of the manuscripts that belong in the highest-value 20% have the misfortune to elicit rejections from as many as five journals. Some social science departments and business schools strongly emphasize publication in prestigious journals. Although one can draw inferences about an author’s average manuscript from the percentage in top-tier journals, the confidence limits for such inferences are wide. A focus on prestigious journals may benefit the most prestigious departments or schools but add randomness to the decisions of departments or schools that are not at the very top. Such a focus may also impede the development of knowledge when mediocre research receives the endorsement of high visibility.